Antimicrobial Activities and Toxicities of the Leaf Extracts of Ficus nota (Blanco) Merr. - Latayada, Felmer S.; Uy, Mylene M. (Asian Journal of Biological and Life Sciences, 2016)
The antimicrobial activities and cytotoxic potentials of the ethanol, hexane, chloroform and aqueous extracts of the Philippine medicinal plant F. nota was evaluated using disc diffusion assay and brine shrimp lethality assay, respectively. The aqueous extract (FnA) showed active to very active levels of inhibition against the three bacterial test organisms B. subtilis, S. aureus, and E. coli, with zones of inhibitions ranging from 18.7±1.15 mm to 20.0±0.00 mm. The extract FnA further exhibited activity against the two fungi S. cerevisiae (11.7±1.15 mm, partially active) and C. albicans (14.0±1.00 mm, active). This significant antimicrobial results of the aqueous extract was followed by the chloroform extract, FnC (17.0±5.2 mm, active against B. subtilis and 22.3±4.62 mm, very active against S. aureus). Meanwhile, the toxicity test showed that the ethanol extract FnE scored significant toxicities against the test organism Artemia salina with LC50 values of 79.43 g/ml and 206.5 g/ml, respectively. This study shows that the bioactive components of F. nota with antibacterial, antifungal, and potential cytotoxic properties were successfully and effectively extracted and concentrated in the various leaf extracts. These findings further support the ethno-medicinal uses of F. nota.
Keywords: Anticancer; Antimicrobial; cytotoxicity; Medicinal plant; Synergistic effects